ANALISIS JARINGAN TAGAR #IKUTPAKDEPRABOWO-GANJAR PADA MEDIA SOSIAL MENGGUNAKAN NETLYTIC TOOLS - Robing Robing; Aprilia Natasya; Silvia Yulianingsi (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2023)
One of the social media platforms that has significantly impacted the Prabowo-Ganjar controversy as the presidential tandem in 2024 is Twitter. Due to the initiatives of various Twitter accounts to popularize and support the issue of Prabovo-Gangjar as the presidential candidate duo in Pilpres 2024, the hashtag #IkutPakdePrabowo-Ganjar arose and started trending on Twitter. The buzzer's part in making the Prabowo-Ganjar controversy popular, particularly on social media, The research looked at tweets that used the hashtag #ikutPakdePrabowo-Ganjar. Through the use of netlytic.org technologies, which were tracked from March 9 to March 15, 2023, the researchers made observations and gathered data. The hashtag #FollowPakdePrabowo-Ganjar encourages these two politicians to run for vice president and president in 2024. The Social Network Analysis (SNA) approach is used in this study to visualize social networks using Netlytic tools by crawling 2500 tweets' worth of data. The findings showed that the inclusion of a buzzer function might make the average data from the same caption and the conclusion from the #IkutPakdePrabowo-Ganjar tag a popular topic. As the 2024 presidential duo, there is active public discussion of Prabowo-Ganjar on Twitter. Buzzers and political activists utilize the Twitter platform to express their support, disapproval, and opinions on the subject.